Morphological characteristics of streamer region for long air gap positive discharge. (22nd October 2020) - Gu, Jianwei; Huang, Shengxin; Fu, Yufei; Chen, Weijiang; Cheng, Dengfeng; Shi, Weidong; Fu, Zhong; Pei, Zhehao; Fan, Xing; He, Tianyu
Abstract: Knowledge of leader corona is the basis for long spark discharge modelling, which is critical to understand the underlying physics of lightning flashes and dielectric breakdown of long air gap widely utilized in power systems. This paper presents an accurate observation of the leader corona. The morphology of the leader corona region during the discharge was obtained using a high-speed camera and an image-enhanced charge-coupled device camera. Statistical results showed that the morphology of the streamer region varied at different discharge sub-phases. The first corona was a conical region with the average apex angle of 118.91°; the leader corona region behaved as a cone with an average vertex angle of 75.87° during the leader propagation process; the streamer area in the final jump was a combination of a cylinder and a cone with the average vertex angle of 82.61°. Noting that the obtained cone apex angle of the leader corona during the leader propagation phase was significantly smaller than that in photographical reports, and the observation results were related to the selected temporal resolution of the optical image apparatus. The discussion on the effect of the single-frame exposure time on observation results found that the average vertex angle of the conical streamer region gradually decreased with the decrease of the single-frame exposure time, and eventually tended to a stable value of about 75.96°. For comparison purposes, discharge experiments under two gap-distances demonstrated that on the premise of stable leader, the statistical distribution characteristics of the leader corona vertex angle were consistent, indicating the universal applicability to the simulation researches. Finally, it is found that the distortion of the electric field caused by the space charge explained the variation of the streamer area during the discharge process.